Pengaruh Pemberian Pupuk Kandang Dan Organik Pada Kelembapan Tanah - Lawolo, Toni Yusman (Jurnal Ilmu Pertanian dan Perikanan, 2025)
Soil moisture is a vital factor in supporting plant growth and land productivity. One effort to maintain and enhance soil moisture is through the application of manure and organic fertilizers. This study aims to systematically examine the effects of manure and organic fertilizers on soil moisture based on previous research findings. The method employed is a literature review by analyzing various relevant sources, including scientific journals, textbooks, and research reports. The results indicate that manure and organic fertilizers can improve soil moisture through enhancements in soil structure, aggregation, resistance to evaporation, and water retention capacity. The combination of organic fertilizer use and proper application management has been shown to yield more optimal results in preserving soil moisture. Therefore, the use of manure and organic fertilizers is an effective and sustainable solution for maintaining soil quality, especially in agricultural areas prone to drought.